A qualitative study of children who have been sexual abused in Tawau - Nur Athirah, Affendi (Universiti Malaysia Sarawak (UNIMAS), 2018)
Children sexual abuse has become phenomenon in all over the world. For this, the researcher is focusing on the phenomenon of sexual abuse among children that has been sexually abused as the main point for this research. Child sexual abuse (CSA) is a sexual activity that involved a children and the perpetrators which the victims do not understand the act of the sexual activity. This sexual activity is done by someone who has sexual desires toward children. Generally, this research was described the phenomenon among the children who have been sexually abused and focusing on socio-demographic profile of the victims, to describe the life experiences of the abused victims, to investigate the effects of sexual abuse on the abused victims and to study the parents of the victims. This research was be conducted by using a qualitative design which four informants will interviewed in this research study. These four informant were selected using the snowball sampling and all the data that obtained from the interview will be analyzed using the content analysis. The findings shows that the perpetrator was among their relative and someone close to the children. Children who have experienced child sexual abused and their parents are both being psychologically affected. This research recommends for the future researches to expand the scope of the research, to study the adult who have experienced sexual abuse during childhood.